New multicentre point charge models for molecular electrostatic potentials from semiempirical MO-calculations - Gedeck, Peter; Schindler, Thorsten; Alex, Alexander; Clark, Timothy (Journal of Molecular Modeling, 2000)
Two quasi-multipole electrostatic models for molecular charge distributions are presented. They assign arrays of point charges to nonhydrogen atoms on the basis of hybrid orbitals or localised molecular orbitals. When used with common semiempirical MO-techniques, they reproduce natural atomic orbital derived point charge (NAO-PC) and ab initio molecular potentials well. The localised orbital technique (LMO-PC) is intuitively more attractive than the hybrid orbital-point charge (HO-PC) method, although the former is more CPU-intensive.
Keywords: molecular electrostatic potential; AM1; PM3; MNDO; point charge model